Differences in Body Composition between Water Polo Players (U18) of the Southeast Europe Top Clubs - Gardasevic,Jovan (Sociedad Chilena de Anatomía, 2021)
SUMMARY: This research aimed to determine the differences between the junior (U18) water polo players of five Croatian and one Montenegrin clubs in the anthropometric characteristics and body composition. The first sample of the subjects consisted of 14 players of the water polo club Mladost average age 17.57±0.65, the second sample consisted of 11 players of the water polo club Sibenik (17.82±0.65), the third sample consisted of 13 players of the water polo club Primorje (17.23±1.01), the fourth sample consisted of 15 players of the water polo club Mornar (17.13±0.64), the fifth sample consisted of 13 players of the water polo club Medvescak (17.92±0.76) and the sixth sample consisted of 10 players of the water polo club Jadran Herceg Novi (Montenegro) (17.70±1.34). In the 2010-11 season, these clubs participated in Regional Water Polo League, commonly known as the Regional League or Adriatic League in Southeast Europe. The measurements was conducted in the competition season in the period September-December 2010, at sports centers and swimming pools of water polo clubs that participated in the research. Anthropometric characteristics and body composition were evaluated using a battery of 12 variables: body height, body weight, arm length, arm span, leg length, foot length, chest skinfold, triceps skinfold, back skinfold, abdominal skinfold, upper leg skinfold and body mass index. The standard central and dispersion parameters of all variables were calculated. The significance of the differences between the water polo players of six teams in the variables for assessing anthropometric characteristics and body composition were determined using ANOVA and an LSD Post Hoc test.Based on the central and dispersion parameters, it can be stated that the values of all the variables are highly similar to all of the water polo players of these six clubs. The ANOVA test found that the water polo players of the six international clubs do not have statistically significant differences in the variables for assessing anthropometric characteristics and body composition.